?STUDIES ON THE CONTROL OF POWDER-POST BEETLES (LYCTUS SPP) BY INDIG- ENOUS PESTICIDE IN COMPARISON TO DDT AND BHC (Biological Sciences - PJSIR, 2000)
Studies were conducted with a view to promoting indigenous pesticides for the control of Lye/us spp (powder-post beetles). Tenekil (A multichlorinated hydrocarbon, developed and formulated at PCSIR Laboratories Complex, Karachi) at the doses of 0.5%, 1%& 1.5% gave 58%, 71.6% & 94% mortality of Lye/us powder-post beetle in different infested wooden samples under laboratory conditions after 24 h. DDT at the same concentrations gave 40%, 43.3% and 58.3% mortality, whereas BHC gave slightly higher mortality i e 45.6%,51.6% and 60.3%.